Conjugated polymers : properties, processing, and applications - Reynolds, John R., 1956-; Thompson, Barry C.; Skotheim, Terje A., 1949- (CRC Press, 2019)
This book covers properties, processing, and applications of conducting polymers. It discusses properties and characterization, including photophysics and transport. It then moves to processing and morphology of conducting polymers, covering such topics as printing, thermal processing, morphology evolution, conducting polymer composites, thin films
Keywords: Conducting polymers.; Organic conductors.; elektronické knihy; electronic books